PSIKOLOGI SASTRA DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Eni Marlina (Universitas PGRI Palembang, 2017)
Novel can be understood by studying from various aspects and approach one of them by using approach of Literary Psychology. Research in the Novel of the Moon Split in the sky of America by Hanum Salsabiela Rais and Rangga Almahendra is focused on Personality figures included in the type of id (Das Es), Ego (Das Ich) and Super Ego (Das Ueber Ich) according to the theory of Sigmund Freud, Based on the results of research related to the study of literary psychology in novel Moon Splitted in the Sky American by Hanum Salsabiela Rais and Rangga Almahendra can be put forward as follows (1) Story in the novel of the Moon Split in the Sky America The work of Hanum Salsabiela Rais and Rangga Almahendra is centered on the central figure, whereas the additional figure of the writer described by the author is seen as a result of the actions performed by the main mat (2) the personality of the figure based on Singmund Freud's theory in the novel of the Spherical Moon in the Sky America In accordance with the problem formulation that is (a) aspect Id (Ice Dai) which includes change facial expression to (B) Ego (Das Ich) which is the nature and feelings of the characters such as the feeling of annoyance, sadness, and sadness , Tortured, and happy, (c) Super ego (Das Ueber Ich) embodied in the form of interaction of the characters with others, remind each other in the goodness, and the internal conflict that occurs within the characters and kinflik that occur between characters with characters Others. Keywords: Psychology, Literature, Moon novel Split in American Skies